Case Report: Improvement of diplopia due to severe internuclear ophthalmoplegia by 4-aminopyridine documented using a novel virtual reality-based oculography headset - Reuter, Emilie; Luerweg, Justus; Schneider, Ruth; Klimas, Rafael; Motte, Jeremias; Gold, Ralf; Salmen, Anke (Frontiers in Virtual Reality, 2025)
Internuclear ophthalmoplegia (INO) is an eye movement disorder that occurs in approximately one-third of people with multiple sclerosis (MS). We used a novel, head-mounted, virtual reality (VR)-based oculography device (PRET™, machineMD AG, Switzerland) to objectively measure oculomotor symptoms reported by a patient with MS to aid in the clinical diagnosis confirmation of INO. The patient’s symptoms, primarily diplopia, were managed successfully with 4-aminopyridine. The VR-based eye-tracking tool documented the subjective improvement in oculomotor function tracking treatment effects.